Incidence of dysphotopsia following uneventful cataract surgery [phacoemulsification] in patients implanted with different types of monofocal intraocular lenses - Khalid Saeed Abdulmajeed; Mohammed Nidham Abdalla; Tara Mahmood Hassan (Advanced Medical Journal)
Background and objectives: Pseudophakic dysphotopsia is one of the major causes of patient dissatisfaction after cataract surgery. Our aim was to assess the incidence of dysphotopsia after phacoemulsification with implantation of three types of monofocal intraocular lenses.